The Perception of the Myth of Occident in Migjeni’s Work - Avdullaj, Valbona Gaçe (ANGLISTICUM. Journal of the Association-Institute for English Language and American Studies, 2016)
The modernism in European Literature was preceded by historical developments determined by the intellectual revolution that put in question the metaphysical thought of the previous European tradition. Modernism has become a literary movement that reflects the innovation of the creation on the ruins of the previous tradition. L’Occident as a new modern spirit with the intellectual development of emancipation has become as a myth for the small nations. The Albanian Literature, dominated theretofore by a tradition of the national spirit, well known as the Albanian Renaissance, feels the pressure of these changes, reflecting it through creations of Albanian authors that have been educated in the West. Although this literature has inherited the feature of delay compare to other westerns literature, these authors, attracted from the changes the literature was going through, dare to write in different literary European trends. The myth of Occident in the work of Migjeni has been observed since in the beginning from the scholar Arshi Pipa … "as an epochal vocation..." Migjeni has sensed the new European spirit, not only as a magnetic attraction to new sudden developments but as a movement to destroy entrenched systems of thought that were returned to the myth of peoples for centuries. He did come as a wrecker of its cultural tradition, but not as much as a result of his own choice of being in the footsteps of his followers95 rather than as the direct result of his consciousness of being subjected to a powerful temptation; to rise against the ancient myth as the world itself is, which shocks the foundation of faith upon which was built the whole European civilization. The myth of Occident to Migjeni is represented to readers as an expression of the will of detachment from the "rule" and the influence of the Christian religion. Keywords: modernism, tradition, delay, myth, the myth of Occident, Christian religion.